1985
DOI: 10.1271/bbb1961.49.3189
|View full text |Cite
|
Sign up to set email alerts
|

Effectors differently modulating the dextransucrase activity of Leuconostoc mesenteroides.

Abstract: Effects of various compounds on the dextransucrase (EC 2.4.1.5) from Leuconostoc mesenteroides was evaluated based on the two catalytic activities of enzyme,that is the hydrolase activity for the substrate, sucrose, and the transferase activity of a D-glucosyl group to an acceptor molecule. Theeffectors were grouped into six categories by their activation or inhibition of the sucrase and transferase activities of dextransucrase. Type I-A inhibited both activities, type I-B inhibited the sucrase activity, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…It has been proposed that glucan is bound to the enzyme through non‐covalent links [38]. More recently, results coming from inhibition kinetic studies using various agents suggested that the glucan binding site was separated from the sucrose binding site [47–51]. This hypothesis has also been confirmed by the identification of glucansucrase sequences and by structure–function relationship studies (see ).…”
Section: Mechanism Of Glucansucrase Actionmentioning
confidence: 89%
“…It has been proposed that glucan is bound to the enzyme through non‐covalent links [38]. More recently, results coming from inhibition kinetic studies using various agents suggested that the glucan binding site was separated from the sucrose binding site [47–51]. This hypothesis has also been confirmed by the identification of glucansucrase sequences and by structure–function relationship studies (see ).…”
Section: Mechanism Of Glucansucrase Actionmentioning
confidence: 89%
“…Another substance that can inhibit the growth of L. mesenteroides, sodium dodecylsulfate (SDS), also known as lau- ryl sulfate, was added to solutions containing 15 g/L sucrose. SDS was chosen as a growth inhibitor because of its documented success in reducing the effectiveness of sucrose cleavage by dextransucrase (Kobayashi et al, 1985). For the conditions used in the growth experiments, the SDS critical micelle concentration (CMC), was approximately 0.8 mM (Hiemenz and Rajagopalan, 1997).…”
Section: Sodium Dodecylsulfate Inhibitionmentioning
confidence: 99%
“…Some are mentioned briefly in the following. Kobayashi et al suggested that the dextransucrase reaction should be separated into sucrase and transferase steps with respect to the action of effectors [31]. We follow the theory of the insertion mechanism assumed by Ebert and Schenk as well as Kindler and Ludwig and later on extended by Robyt et al: The glucosyl moiety of the substrate sucrose is linked covalently to dextransucrase and simultaneously fructose is released.…”
Section: Insertion Mechanism and Acceptor Reactionmentioning
confidence: 96%